DOKTER KECIL: STUDENT EMPOWERMENT THROUGH LEARNING FIRST AID SKILL AND KNOWLEDGE - Indarwati, Retno; Astuti, Trihaningsih Puji; Basri; Lutfiandini, Cherlys Tin; Choiriyah, Lilik; Nurmalaningsih, Ucik; Sa'diyah, Halimatus; Resubun, Clara Cassandra; Amelia, Vira; Nugrahanto, Muhamad Rafly Bagus; Handayani, Nurul Fauziah; Kurniawati, Tya Wahyun (Universitas Airlangga, 2024)
Introduction: Knowledge and skills of simple first aid are packaged by the UKS program through the role of Dokter Kecil. Interactive learning using video, demonstration and simulation activities has increased first aid knowledge and skills in primary school students. The aim of this community service program was to increase first aid knowledge and skills of wound care, nosebleed and syncope in school age children. Methods: The community service was conducted at SDN Komplek Kenjeran II in Surabaya, Indonesia, involving 40 students from grades 3 to 5. The intervention was provided in a 4-hour session, using video demonstrations and hands-on simulation. Pre-test and post-test questionnaires measured students' knowledge and attitudes before and after the training. Data were analyzed using descriptive statistics. Results: The demographic characteristics of participants were dominated by the age 10 years (37.5%), in fourth grade (42.5%) and female (62.5%). The average pre-test knowledge score was 65 and pre-test attitude score was 76.4. After doing interactive learning, demonstrations and simulations, the average student post-test score experienced a significant increase, namely 84.5 in the knowledge and 89.7 in the attitude. Conclusion: The Dokter Kecil program significantly improved students’ skills and knowledge in managing wound care, nosebleeds, and syncope. This empowerment program demonstrates the effectiveness of interactive learning in fostering critical first aid skills in school-aged children. Regular updates to the training content are recommended to ensure ongoing relevance and efficacy.